Sublethal effects of chlorantraniliprole on molting hormone levels and mRNA expressions of three Halloween genes in the rice stem borer, Chilo suppressalis. (January 2020) - Meng, Xiangkun; Zhang, Nan; Yang, Xuemei; Miao, Lijun; Jiang, Heng; Ji, Caihong; Xu, Beibei; Qian, Kun; Wang, Jianjun
Abstract: While sublethal effects of insecticide on insect development have been widely studied, the underlying mechanisms remain elusive. Our previous studies revealed that sublethal concentrations of chlorantraniliprole significantly increased the juvenile hormone levels and resulted in both prolonged developmental time and reduced fecundity in Chilo suppressalis . In the present study, we evaluated the sublethal effects of chlorantraniliprole on molting hormone (MH) levels and mRNA expressions of three Halloween genes including CsCYP307A1, CsCYP306A1 and CsCYP314A1 in C. suppressalis. The results showed that the MH levels in different developmental stages of C. suppressalis were decreased after exposure to LC10 and LC30 of chlorantraniliprole. However, analysis of temporal expression profiles revealed that the mRNA levels of three Halloween genes were not closely correlated with the ecdysteroid titers in C. suppressalis . Notably, the transcript levels of CsCYP307A1, CsCYP306A1 and CsCYP314A1 were induced after treatment with sublethal concentrations of chlorantraniliprole in specific developmental stages. These results indicated that chlorantraniliprole had adverse effects on insect MH biosynthesis, and in addition to the involvement in MH biosynthesis, CsCYP307A1, CsCYP306A1 and CsCYP314A1 may also play important roles in the detoxification metabolism of chlorantraniliprole in C. suppressalis . Graphical abstract: Image 10955 Highlights: The MH levels in C. suppressalis were decreased after exposure to LC10 and LC30 of chlorantraniliprole. The mRNA levels of three Halloween genes were not closely correlated with the ecdysteroid titers in C. suppressalis. CsCYP307A1, CsCYP306A1 and CsCYP314A1 were induced after treated with sublethal concentrations of chlorantraniliprole.